Early versus late MCI: Improved MCI staging using a neuropsychological approach. Issue 5 (5th February 2019) - Edmonds, Emily C.; McDonald, Carrie R.; Marshall, Anisa; Thomas, Kelsey R.; Eppig, Joel; Weigand, Alexandra J.; Delano‐Wood, Lisa; Galasko, Douglas R.; Salmon, David P.; Bondi, Mark W.; ,
Abstract: Introduction: The Alzheimer's Disease Neuroimaging Initiative (ADNI) separates "early" and "late" mild cognitive impairment (MCI) based on a single memory test. We compared ADNI's MCI classifications to our neuropsychological approach, which more broadly assesses cognitive abilities. Methods: Three hundred thirty‐six ADNI‐2 participants were classified as "early" or "late" MCI. Cluster analysis was performed on neuropsychological test data, and participants were reclassified based on cluster results. These two staging approaches were compared on progression rates, cerebrospinal fluid biomarkers, and cortical thickness profiles. Results: There was little correspondence between the two staging methods. ADNI's early MCI group included a large proportion of false‐positive diagnostic errors. The reclassified neuropsychological MCI groups showed steeper survival curves and more abnormal biomarkers. Conclusions: Our novel neuropsychological approach improved the staging of MCI by (1) capturing individuals at an early symptomatic stage, (2) minimizing false‐positive cases, and (3) identifying a late MCI group further along the disease trajectory.